Analysis of Professional Specialization in the Perspective of Islamic Economic Philosophy - Burhanuddin Al-Butary; Luthfiah Hanifah; Septrita Sutriyani; Ahmad Fadil Noval (Penerbit Jurnal Indonesia, 2023)
The study's goal was to define the concept of work professionalism in Islamic economics and to determine the characteristics of professional Muslims in the workplace. The library is the primary location for research. Information is gathered by library research, more specifically by amassing texts on Islamic economics that take a stance on the professionalism of the workplace. Content analysis is used in the methodology for analyzing the data, which is subsequently selected, displayed, and processed in depth. The results show that the idea of professionalism in the workplace in Islamic economics can be seen as the attitude of always taking one's work seriously. Working hard, working full time, exercising discipline, being honest, having strong loyalty, and dedicating oneself totally to one's work are all components of this philosophy. Both ihsan and itqon (professionalism) are highly commended in Islam. Muslims are encouraged by their faith to work in a wide variety of professions and locations. Since Muslims view their job as a religious act, they always put up their best effort, which is congruent with characteristics of a disciplined work ethic. In the context of Islamic economics, there are three primary traits that indicate whether or not a Muslim is professional in their line of work: professional (kafa'ah), as evidenced by skill in one's chosen field; dedicated to one's work; and appreciative of the opportunities afforded by one's vocation. Trust, which is shown in a responsible and trusted attitude when executing each work or obligation, is a blessing from Allah SWT and a prerequisite for its honest and grateful operation. Knowledgeable performance; this is what the Arabic word kafa'ah refers to. According to the Islamic ideals taught by Nabiyullah Muhammad SAW, the virtues of honesty (shiddiq), accountability (amanah), a communicative nature (tabligh), and intelligence (nature) can serve as a basis for professional growth (fathanah).